The Human Spirit Groundwork - McGaughey, Douglas R. (African Sun Media, 2017)
An integrated collaborative work and a valuable source for understanding the underpinnings of the concept of spirituality that self-proclaims the "audacious" task of reformulating how we think about Spirit. It is about creative capacities, mind/brain, causality, free will, morality, consciousness, and beauty. In short, it is about being human.